Perspectives on Implications of ChatGPT on Teaching, Learning, Research and Innovation in the Higher Education Sector - Netswera, Fulufhelo; Zungu, Lindiwe (New Voices in Psychology, 2023)
As of 16 March 2023, 26,222 prominent entrepreneurs and business executives had signed a petition to cease all Artificial Intelligence (AI) experimentation and training beyond GPT-4.”[1] The rationale for this intervention was to examine the impact of AI developments and whether they pose a major risk to humanity. The petitioners believe that current AI developments can compete with humans in almost all respects and caution that AI technological advancements can lead to developments beyond human control with a high potential to outsmart humans. Teaching and learning (T&L), research and innovation form the backbone of the higher education sector. Higher education institutions develop individuals' intellectual, operational and technical abilities for a functional society. By its definition, a higher education institution and a university in particular is a provider of facilities and resources that enable intellectuals and expertise to facilitate T&L, research and community engagement.[2] Recently, the question of community engagement viewed in respect of its earlier reference to the triple helix has been redefined into quad helix as “engagement” to embrace all “stakeholders”. Here, mutual T&L between the higher education sector and industries continues to increase learning machine technologies for operational purposes in agriculture, manufacturing, and packaging.[3]